High performance of a novel point-of-care blood test for Toxoplasma infection in women from diverse regions of Morocco. Issue 1 (1st January 2021) - El Mansouri, Bouchra; Amarir, Fatima; Peyron, François; Adlaoui, El Bachir; Piarroux, Raphaël; Lykins, Joseph; El Abbassi, Majda; Nekkal, Nesma; Bouhlal, Nadia; Makkaoui, Kamar; Barkat, Amina; Lyaghfouri, Aziza; et al.
ABSTRACT: Point-of-care (POC) testing for Toxoplasma infection has the potential to revolutionize diagnosis and management of toxoplasmosis, especially in high-risk populations in areas with significant environmental contamination and poor health infrastructure precluding appropriate follow-up and preventing access to medical care. Toxoplasmosis is a significant public health challenge in Morocco, with a relatively heavy burden of infection and, to this point, minimal investment nationally to address this infection. Herein, we analyse the performance of a novel, low-cost rapid test using fingerstick-derived whole blood from 632 women (82 of whom were pregnant) from slums, educational centres, and from nomad groups across different geographical regions (i.e. oceanic, mountainous) of Morocco. The POC test was highly sensitive and specific from all settings. In the first group of 283 women, sera were tested by Platelia ELISA IgG and IgM along with fingerstick whole blood test. Then a matrix study with 349 women was performed in which fingerstick – POC test results and serum obtained by venipuncture contemporaneously were compared. These results show high POC test performance (Sensitivity: 96.4% [IC95 90.6–98.9%]; Specificity: 99.6% [IC95 97.3–99.9%]) and high prevalence of Toxoplasma infection among women living in rural and mountainous areas, and in urban areas with lower educational levels. The high performance of POC test confirms that it can reduce the need for venipuncture and clinical infrastructure in a low-resource setting. It can be used to efficiently perform seroprevalence determinations in large group settings across a range of demographics, and potentially expands healthcare access, thereby preventing human suffering.